(untitled) (Historia, 2021)
1. Joseph Lehmann: The First Boer War 2. Percy M. Clark: The Autobiography of an old Drifter 3. E. C. Tabler: James Chapman, Travels in the Interior of South Africa 4. D. J. Roorda: Het rampjaar 1672 5. Marius J. Swart: Wereldleiers